Pengaruh Kualitas produk, Fitur, Dan Desain Terhadap Keputusan Pembelian Pada Mebel Jati Ukir Hi. Slamet Di Metro - Ali, Ahmad Sefrian; Yateno, Yateno (Jurnal Manajemen DIVERSIFIKASI, 2022)
Along with the large demand for products ,furniture manufacturers compete to produc equality product saccording to consumer desires. This study aims to determine the effect of product quality, features, and design on purchasing decisions for Teak Ukir Hi furniture. Good luck on the Metro. The type of research used is quantitative research. The research method used is the explanatory survey method. The data used are questionnaire data and data documentation. The subjects of this research are customers of Jati Ukir Hi. Slamet. Samples were taken as many as 60 respondents. As well as in the data analysis technique using Multiple Linear Regression analysis. Based on the results of the study showed that the product quality, features and design variables on the purchasing decision variables in the hypothesis test simultaneously stated that the Fcount (31.838>Ftable 2.769) and the significance value 0.000 <0.05 then the product quality, features and design variables together positive and significant effect on purchasing decisions. The largest tcount value is 6.898 where this value is in the product quality variable.